Method for producing cationic acrylic resin, cathodically electrodeposition coating film and use thereof

CN122958638APending Publication Date: 2026-10-23ZHEJIANG QUZHOU CHENGJI PAINT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611412797.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004]针对现有的环氧阴极电泳涂料耐候性差、柔韧性不足、固化温度高、透明度有限的技术问题,本发明提出了阳离子丙烯酸树脂的制备方法、阴极电泳涂膜及其应用,通过脂肪族丙烯酸酯类单体与甲基丙烯酸酯类单体的共聚,配合含羟基单体和含叔胺基单体的功能化改性,制得的树脂用于阴极电泳涂料后在160℃下即可交联固化,涂膜兼具优异的耐候性、高透明度、良好柔韧性和3H硬度,实现了阴极电泳涂膜在户外装饰面漆领域的应用

Benefits of technology

[0015]本发明的有益效果是:(1)采用阳离子丙烯酸树脂作为阴极电泳涂料的成膜材料,由于丙烯酸树脂分子结构中对光的主吸收峰位于太阳光谱范围之外,紫外线辐射能量难以被树脂分子有效吸收并引发光化学反应,因此涂膜具有优异的耐光性和耐户外老化性能。在长期户外使用环境下,涂膜不易发生黄变、失光和粉化等老化现象,能够长期保持良好的外观状态和防护性能。这一特性使得本发明制备的阳离子丙烯酸树脂阴极电泳涂膜不仅能够用作底漆,还可以直接作为面漆使用,实现底面合一涂装,从而克服了传统环氧阴极电泳涂膜仅能用作底漆的局限性,显著拓展了阴极电泳涂料在户外高耐候要求领域的应用范围。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958638A_ABST
    Figure CN122958638A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of cationic acrylic resin, a cathodic electrophoretic coating film and application of the cationic acrylic resin. The method uses a mixture of a tertiary amine group-containing monomer, a hydroxyl group-containing monomer, a methacrylic ester monomer and an acrylic ester monomer as a copolymer monomer, adopts a free radical polymerization continuous dropping process, polymerizes for 3.5-4.0 hours at 85-95 DEG C, supplements an initiator, and insulates for 1.5-2.0 hours, then after cooling, the mixture is neutralized to a neutralization degree of 75+ / -5% by adding an organic acid, and the cationic acrylic resin is obtained. The resin is prepared into a cathodic electrophoretic coating material with an isocyanate curing agent, and after crosslinking and curing at 160 DEG C for 30 minutes, the coating film formed has excellent weather resistance, high transparency, good flexibility and 3H pencil hardness, and overcomes the defects of traditional epoxy cathodic electrophoretic coating materials, such as poor weather resistance, easy yellowing and powdering, large brittleness of the paint film, high curing temperature and poor decorative effect, and can be widely used in the coating of metal workpieces in the fields of hardware, household appliances and building materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of coating technology, specifically to a method for preparing cationic acrylic resin, cathodic electrophoretic coating, and its application. Background Technology

[0002] Epoxy cathodic electrophoretic coatings are widely used as anti-corrosion primers for indoor and outdoor metal parts due to their advantages such as strong anti-corrosion ability, excellent metal adhesion, high penetration, paint hardness and wear resistance, mature industrialization and low cost, as well as resistance to salt water, humid heat and alkaline media. They are also widely used as anti-corrosion primers for metal parts such as automobile chassis, fasteners, construction machinery, and hardware and home appliances.

[0003] However, epoxy cathodic electrophoretic coatings have the following drawbacks: a) The epoxy resin molecular chain contains aromatic structures, which are prone to yellowing, loss of gloss, and chalking under ultraviolet irradiation, resulting in poor weather resistance. Therefore, they are only suitable as primer coatings and cannot be used alone as outdoor decorative topcoats; b) Epoxy resins have a high crosslinking density, resulting in brittle and inflexible paint films that are prone to microcracks under alternating hot and cold environments, affecting the long-term protective performance of the coating; c) Epoxy cathodic electrophoretic coatings require high curing temperatures and consume a lot of energy during baking, which is not conducive to energy conservation and environmental protection; d) Epoxy cathodic electrophoretic coatings have limited transparency, poor pigment adaptability, and poor decorative effects, making them difficult to meet the requirements of high-decorative applications. Summary of the Invention

[0004] To address the technical problems of existing epoxy cathodic electrophoretic coatings, such as poor weather resistance, insufficient flexibility, high curing temperature, and limited transparency, this invention proposes a method for preparing cationic acrylic resin, a cathodic electrophoretic coating film, and its application. Through copolymerization of aliphatic acrylate monomers and methacrylate monomers, combined with functional modification with hydroxyl-containing monomers and tertiary amine-containing monomers, the resulting resin can be crosslinked and cured at 160℃ when used as a cathodic electrophoretic coating. The coating film exhibits excellent weather resistance, high transparency, good flexibility, and 3H hardness, enabling the application of cathodic electrophoretic coating films in the field of outdoor decorative topcoats.

[0005] The technical solution adopted in this invention is as follows: A method for preparing cationic acrylic resin, comprising the following steps: S1. The first part of the oil-soluble initiator is dissolved in the monomer mixture, and the polymerization reaction is carried out by a continuous drop-addition process of free radical polymerization. The polymerization reaction temperature is 85~95℃ and the polymerization time is 3.5~4.0 hours. S2. After the polymerization reaction is completed, add the second part of oil-soluble initiator and keep it at the temperature for 1.5 to 2.0 hours. The sum of the mass of the first part of oil-soluble initiator and the second part of oil-soluble initiator accounts for 1-5% of the mass of the monomer mixture. S3. Cool down to 60~70℃, add organic acid to neutralize until the degree of neutralization is 75±5%, keep warm for 20~40 minutes and then discharge to obtain cationic acrylic resin; The monomer mixture includes monomers containing tertiary amine groups, monomers containing hydroxyl groups, methacrylate monomers, and acrylate monomers. The total mass of the monomer mixture is denoted as M. The monomers containing tertiary amine groups account for 10-15% of M. The monomers containing hydroxyl groups account for 15-20% of M. The mass ratio of the methacrylate monomers to the acrylate monomers is (4-3):2, and the sum of their masses accounts for 65-75% of M.

[0006] Optionally, the monomer containing a tertiary amine group is selected from one or more of dimethylaminomethyl methacrylate, dimethylaminoethyl methacrylate, and dimethylaminoethyl acrylate.

[0007] Optionally, the hydroxyl-containing monomer is selected from one or more of hydroxyethyl methacrylate, hydroxypropyl methacrylate, and hydroxypropyl acrylate.

[0008] Optionally, the acrylate monomer is selected from one or more of ethyl acrylate, propyl acrylate, butyl acrylate, and isooctyl acrylate.

[0009] Optionally, the methacrylate monomers are selected from one or more of methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, n-octyl methacrylate, and isooctyl methacrylate, or the methacrylate monomers may be partially or completely replaced with styrene.

[0010] Optionally, the first portion of the oil-soluble initiator is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile, and benzoyl peroxide, and the second portion of the oil-soluble initiator is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile, and benzoyl peroxide.

[0011] Optionally, in step S1, an organic solvent is used to dissolve the monomer mixture and the first portion of the oil-soluble initiator; in step S2, the second portion of the oil-soluble initiator is dissolved in an organic solvent and then added; the mass of the organic solvent accounts for 50±5% of the mass of the cationic acrylic resin; the organic solvent is selected from one or more of ethylene glycol butyl ether, propylene glycol methyl ether, and isopropanol; the organic acid is selected from one or more of formic acid, acetic acid, and lactic acid.

[0012] Optionally, in step S1, the first portion of the oil-soluble initiator and the monomer mixture are first dissolved together in the first portion of the organic solvent, and then added dropwise to the reaction system at a constant pressure dropping funnel to carry out the free radical polymerization continuous dropping process.

[0013] The present invention also discloses a cathodic electrophoretic coating, comprising an isocyanate curing agent, water, and a cationic acrylic resin prepared by any one of claims 1 to 9, wherein the mass ratio of the cationic acrylic resin, the isocyanate curing agent, and the water is (50 to 70):(15 to 30):(300 to 450).

[0014] The present invention also discloses an application of the cathodic electrophoretic coating as described above, wherein the cathodic electrophoretic coating is applied to the surface of a metal workpiece and baked at 140~170℃ for 20~40 minutes to form a cured coating.

[0015] The beneficial effects of this invention are: (1) Cationic acrylic resin is used as the film-forming material of cathodic electrophoretic coating. Since the main absorption peak of light in the molecular structure of acrylic resin is located outside the solar spectrum, the ultraviolet radiation energy is difficult to be effectively absorbed by the resin molecules and trigger photochemical reactions. Therefore, the coating has excellent light resistance and outdoor aging resistance. Under long-term outdoor use, the coating is not prone to yellowing, loss of gloss and chalking and other aging phenomena, and can maintain a good appearance and protective performance for a long time. This characteristic makes the cationic acrylic resin cathodic electrophoretic coating prepared by this invention not only usable as a primer, but also usable directly as a topcoat, realizing a combined primer and topcoat coating, thereby overcoming the limitation that traditional epoxy cathodic electrophoretic coating can only be used as a primer, and significantly expanding the application range of cathodic electrophoretic coating in outdoor high weather resistance fields.

[0016] (2) The cationic acrylic resin molecular chain contains both hydroxyl and tertiary amine groups. The hydroxyl group acts as an active site for crosslinking reaction, while the tertiary amine group acts as an internal catalyst for the crosslinking reaction, promoting the urethane esterification reaction between the hydroxyl group and the isocyanate group. Under the synergistic effect of this dual action, the crosslinking reaction between the resin and the isocyanate curing agent can be fully completed under baking conditions of 160℃ for 30 minutes. The curing temperature is lower than that of some traditional epoxy cathodic electrophoretic coatings. The lower curing temperature means a reduction in the heat load of the baking equipment and a reduction in energy consumption. It also helps to reduce the thermal impact on the metal substrate and reduce the risk of substrate deformation or performance degradation caused by high-temperature baking. It has good energy-saving and environmental protection benefits and economic efficiency in industrial applications.

[0017] (3) The flexibility of the resin molecular chain is reasonably controlled by copolymerization modification of acrylate monomers and methacrylate monomers. Acrylate monomers have long side chains and strong molecular chain segment mobility, which can provide good flexibility for the copolymer; methacrylate monomers provide high rigidity. The two are copolymerized at a specific mass ratio (4~3):2, so that the final resin molecular chain achieves a reasonable balance between rigidity and flexibility. At the same time, by introducing hydroxyl-containing monomers and tertiary amine-containing monomers, an appropriate amount of crosslinking active sites are distributed on the resin molecular chain. The three-dimensional network structure formed after crosslinking has sufficient crosslinking density to ensure the hardness and media resistance of the coating film, and is not too brittle due to the toughening effect of acrylate segments. Therefore, the coating film has outstanding flexibility while maintaining high hardness (pencil hardness 3H), and is not prone to microcracks under thermal cycling conditions, which significantly improves the long-term protective reliability and service life of the coating.

[0018] (4) The cationic acrylic resin has a pale yellow and transparent appearance. This is because the acrylic resin molecule does not contain the aromatic chromophores found in epoxy resins, thus exhibiting higher intrinsic transparency. After being formulated into a cathodic electrophoretic coating, the coating film formed by electrophoretic coating is smooth, uniform, and continuous, with high transparency and good gloss, clearly presenting the texture of the metal substrate and fully meeting the high requirements of decorative coatings for the appearance of the paint film. At the same time, the resin has excellent adaptability to pigments, and various pigment pastes can be added as needed to prepare decorative topcoats of different colors without affecting the transparency and gloss of the coating film. These characteristics enable the cathodic electrophoretic coating of this invention to meet the application scenarios with high decorative requirements, and it is suitable for fields such as hardware, home appliances, and building materials where appearance quality requirements are high, realizing the functional expansion of cathodic electrophoretic coatings from primers to decorative topcoats. Attached Figure Description

[0019] Figure 1 The infrared spectrum of the cationic acrylic resin prepared according to Example 1 after drying and solvent removal; Figure 2 This is a graph showing the glass transition temperature of the coating film formed after curing the cationic acrylic resin prepared according to Example 1. Figure 3 This is a schematic diagram of an electrophoretic coating apparatus used for cathodic electrophoretic coating of the present invention. Figure 4 The image shows the physical appearance of the cationic acrylic resin prepared according to Example 1 after cathodic electrophoretic coating, curing and crosslinking.

[0020] The labels in the attached figures are as follows: 1. DC power supply; 2. pH meter; 3. Conductivity meter; 4. Stirrer; 5. Anode plate; 6. Cathode plate. Detailed Implementation

[0021] The present application will now be described in further detail with reference to the accompanying drawings and embodiments.

[0022] Example 1

[0023] The cationic acrylic resin provided in this embodiment is prepared through the following steps: The monomer mixture consists of 10.20 g of methyl methacrylate, 10.20 g of styrene, 13.60 g of butyl acrylate, 10.00 g of hydroxypropyl methacrylate, and 6.00 g of dimethylaminoethyl methacrylate, with a total mass M = 50.00 g. Of this, the monomer containing tertiary amine groups (dimethylaminoethyl methacrylate) accounts for 12.0% of M; the monomer containing hydroxyl groups (hydroxypropyl methacrylate) accounts for 20.0% of M; the mass ratio of methacrylate monomers (the sum of methyl methacrylate and styrene) to acrylate monomers (butyl acrylate) is 20.40:13.60 = 3:2, and the sum of their masses accounts for 68.0% of M.

[0024] S1. Add 20.0g of ethylene glycol butyl ether to a 250mL four-necked flask equipped with a stirrer, reflux condenser, thermometer, and constant pressure dropping funnel, and heat to 80℃. Mix and dissolve 50.00g of the above monomer mixture with 1.00g of azobisisobutyronitrile (the first part of the oil-soluble initiator), and introduce the mixture into the constant pressure dropping funnel. Raise the water bath temperature to 90℃ and start adding the mixture dropwise at a uniform rate. Control the dropping time to 3.5 hours. During the dropping process, the polymerization reaction will proceed through free radical polymerization. S2. After the addition is complete, add 0.20g of azobisisobutyronitrile (the second part of the oil-soluble initiator, which is dissolved in 5.00g of ethylene glycol butyl ether beforehand), and keep warm for another 1.5 hours; the total mass of the first part of the initiator and the second part of the initiator is 1.20g, accounting for 2.4% of M; S3. Cool to 65℃, add 2.20g of glacial acetic acid for neutralization reaction (neutralization degree is 80%), keep warm for 0.5 hours and then discharge to obtain cationic acrylic resin.

[0025] The cationic acrylic resin prepared in this embodiment is pale yellow and transparent. After drying to remove the solvent, it was characterized using an infrared spectrometer. The spectrum shows: 3514 cm⁻¹ -1 The peak at this point is the stretching vibration peak of NH or OH; 2952 cm⁻¹ -1 and 2873cm -1 The peaks represent the stretching vibrations of -CH3 and -CH2, respectively; 1724 cm⁻¹ -1 This is the C=O stretching vibration peak in the ester group; 1452 cm⁻¹ -1 and 1384cm -1 -CH3 and -CH2 deformed peaks appeared at 1143 cm⁻¹, respectively.-1 The peak is the CN stretching vibration peak in the tertiary amine group; while the peak is 1670-1620 cm⁻¹. -1 The absence of characteristic absorption peaks for C=C double bonds within the range indicates that the unsaturated carbon-carbon double bonds in the acrylate monomers have been opened, and all monomers have undergone copolymerization. Differential scanning calorimetry (DSC) measurements show that the glass transition temperature of this resin is 11.5℃.

[0026] Example 2

[0027] The cationic acrylic resin provided in this embodiment is prepared through the following steps: The monomer mixture consists of 12.30 g of propyl methacrylate, 12.20 g of styrene, 16.30 g of butyl acrylate, 12.00 g of hydroxyethyl methacrylate, and 7.20 g of a mixture of dimethylaminomethyl methacrylate and dimethylaminoethyl methacrylate, with a total mass M = 60.00 g. Of this, monomers containing tertiary amine groups account for 12.0% of M; monomers containing hydroxyl groups (hydroxyethyl methacrylate) account for 20.0% of M; the mass ratio of methacrylate monomers to acrylate monomers is approximately 3:2 (24.50:16.30), and the sum of their masses accounts for 68.0% of M.

[0028] S1. Add 20.00g of ethylene glycol butyl ether to a 250mL four-necked flask equipped with a stirrer, reflux condenser, thermometer and constant pressure dropping funnel and heat to 80℃. Mix and dissolve 60.00g of the above monomer mixture with the first part of azobisisobutyronitrile and introduce it into the constant pressure dropping funnel. Raise the water bath temperature to 90℃ and start adding it dropwise at a uniform rate. Control the dropping time to 4.5 hours and carry out the polymerization reaction during the dropping process. S2. After the addition is complete, add the second part of azobisisobutyronitrile (pre-dissolved in 10.00g of ethylene glycol butyl ether), and keep warm for another 3.0 hours; the total mass of the first part of the initiator and the second part of the initiator is 2.00g, accounting for 3.33% of M; S3. Cool to 65℃, add 4.00g of glacial acetic acid for neutralization reaction, keep warm for 40 minutes and then discharge to obtain cationic acrylic resin.

[0029] Example 3

[0030] The cationic acrylic resin provided in this embodiment is prepared through the following steps: The monomer mixture consists of 15.00 g of methyl methacrylate, 15.00 g of styrene, 20.00 g of butyl acrylate, 15.00 g of hydroxypropyl methacrylate, and 10.00 g of dimethylaminoethyl methacrylate, with a total mass M = 75.00 g. Of this, the monomer containing tertiary amine groups (dimethylaminoethyl methacrylate) accounts for 13.33% of M; the monomer containing hydroxyl groups (hydroxypropyl methacrylate) accounts for 20.0% of M; the mass ratio of methacrylate monomers (the sum of methyl methacrylate and styrene) to acrylate monomers (butyl acrylate) is 30.00:20.00 = 3:2, and the sum of their masses accounts for 66.67% of M.

[0031] S1. Add 30.00g of ethylene glycol butyl ether to a 250mL four-necked flask equipped with a stirrer, reflux condenser, thermometer and constant pressure dropping funnel and heat to 90℃. Mix and dissolve 75.00g of the above monomer mixture with the mixture of azobisisobutyronitrile and azobisisoheptanenitrile in the first part (total mass is 2.00g) and introduce it into the constant pressure dropping funnel. Start the uniform dropwise addition and control the dropwise addition time to 4.0 hours. The polymerization reaction is carried out during the dropwise addition process. S2. After the addition is complete, add the second part of the mixture of azobisisobutyronitrile and azobisisoheptanenitrile (total mass 0.50 g, pre-dissolved in 5.00 g of ethylene glycol butyl ether), and keep warm for another 2.0 hours; the sum of the masses of the first part of the initiator and the second part of the initiator is 2.50 g, accounting for 3.33% of M; S3. Cool to 65℃, add 4.50g of glacial acetic acid for neutralization reaction, keep warm for 40 minutes and then discharge to obtain cationic acrylic resin.

[0032] Example 4

[0033] The cationic acrylic resin provided in this embodiment is prepared through the following steps: The monomer mixture consists of 20.00 g of methyl methacrylate, 20.00 g of styrene, 20.00 g of butyl acrylate, 15.00 g of hydroxypropyl methacrylate, and 8.50 g of dimethylaminoethyl methacrylate, with a total mass M = 83.50 g. Of this, the monomer containing tertiary amine groups (dimethylaminoethyl methacrylate) accounts for 10.18% of M; the monomer containing hydroxyl groups (hydroxypropyl methacrylate) accounts for 17.96% of M; the mass ratio of methacrylate monomers (the sum of methyl methacrylate and styrene) to acrylate monomers (butyl acrylate) is 40.00:20.00 = 2:1, and the sum of their masses accounts for 71.86% of M.

[0034] S1. Add 30.00g of ethylene glycol butyl ether to a 250mL four-necked flask equipped with a stirrer, reflux condenser, thermometer and constant pressure dropping funnel and heat to 90℃. Mix and dissolve 83.50g of the above monomer mixture with the first part of azobisisobutyronitrile (1.30g) and introduce it into the constant pressure dropping funnel. Start the uniform dropwise addition and control the addition time to 3.5 hours. The polymerization reaction will take place during the dropwise addition. S2. After the addition is complete, add the second part of azobisisobutyronitrile (0.20g, pre-dissolved in 10.00g ethylene glycol butyl ether), and keep warm for another 2.0 hours; the total mass of the first part of the initiator and the second part of the initiator is 1.50g, accounting for 1.80% of M; S3. Cool to 50℃, add 3.50g of glacial acetic acid for neutralization reaction, keep warm for 30 minutes and then discharge to obtain cationic acrylic resin.

[0035] Example 5

[0036] The cationic acrylic resin provided in this embodiment is prepared through the following steps: The monomer mixture consists of 8.90 g of methyl methacrylate, 18.70 g of styrene, 14.40 g of butyl acrylate, 12.00 g of hydroxypropyl methacrylate, and 8.00 g of dimethylaminoethyl methacrylate, with a total mass M = 62.00 g. Of this, the monomer containing tertiary amine groups (dimethylaminoethyl methacrylate) accounts for 12.90% of M; the monomer containing hydroxyl groups (hydroxypropyl methacrylate) accounts for 19.35% of M; the mass ratio of methacrylate monomers (the sum of methyl methacrylate and styrene) to acrylate monomers (butyl acrylate) is approximately 1.92:1 (27.60:14.40), and the sum of their masses accounts for 67.74% of M.

[0037] S1. Add 22.50g of ethylene glycol butyl ether to a 250mL four-necked flask equipped with a stirrer, reflux condenser, thermometer and constant pressure dropping funnel and heat to 90℃. Mix and dissolve 62.00g of the above monomer mixture with the first part of benzoyl peroxide (1.00g) and introduce it into the constant pressure dropping funnel. Start the uniform dropwise addition and control the addition time to 3.5 hours. The polymerization reaction will take place during the dropwise addition process. S2. After the addition is complete, add the second part of benzoyl peroxide (0.20 g, pre-dissolved in 7.50 g of ethylene glycol butyl ether), and keep warm for another 2.0 hours; the total mass of the first part of the initiator and the second part of the initiator is 1.20 g, accounting for 1.94% of M; S3. Cool to 50℃, add 2.75g of glacial acetic acid for neutralization reaction, keep warm for 30 minutes and then discharge to obtain cationic acrylic resin.

[0038] This invention also provides a cathodic electrophoretic coating and its application. The cationic acrylic resin obtained in Example 1, isocyanate curing agent, and water are mixed at a mass ratio of 60:21:371, and then dispersed in a mixer at a speed of 800 r·min. -1 Disperse the solution for 30 minutes to prepare an emulsion. Add an appropriate amount of black pigment for coloring and stir evenly. Testing showed that the pH of the resulting electrophoretic solution was 5.8–6.2, and the conductivity was 1000–1500 μS / cm, meeting the requirements for electrophoretic coating. A tinplate (50×120×0.35mm) was used as the cathode. The surface oxide layer was removed by sanding with coarse sandpaper, followed by degreasing with organic solvents such as acetone, and then dried. Electrophoresis was performed using an electrophoresis apparatus. The prepared cathodic electrophoretic coating was added to the electrophoresis tank, ensuring proper circulation and no sedimentation. The pretreated tinplate was immersed in the electrophoresis tank as the cathode, and the power was turned on for electrophoretic coating. The electrophoresis voltage was controlled at 60V, and the electrophoresis time at 80s (after optimization, adjusted to 80V and 30–60s). After electrophoresis, disconnect the power supply, remove the cathode sample, immediately rinse off the surface paint with tap water, then rinse thoroughly with deionized water and allow to air dry appropriately. Pre-set the oven temperature to 160℃, place the rinsed sample in the oven and bake for 30 minutes to allow the coating to fully cross-link and cure. Remove the baked sample and allow it to cool naturally for 24 hours to obtain the cured coating.

[0039] Figure 1 This is the Fourier transform infrared spectrum of the cationic acrylic resin (solid resin after drying and solvent removal) obtained in Example 1 of this invention. In the figure: 3514cm -1 The peak at this point is the stretching vibration peak of NH or OH; 2952 cm⁻¹ -1 and 2873cm -1 Stretching vibration peaks for -CH3 and -CH2, respectively; 1724 cm⁻¹ -1 This is the stretching vibration peak of C=O in the ester group; 1452 cm⁻¹ -1 and 1384cm -1 The deformation vibration peaks at 1143 cm⁻¹ are for -CH₃ and -CH₂, respectively. -1 This is the stretching vibration peak of CN in the tertiary amine group. 1670-1620 cm⁻¹ -1 The absence of characteristic absorption peaks for C=C double bonds within the range indicates that the unsaturated carbon-carbon double bonds of the acrylate monomers have been opened, and all monomers have undergone copolymerization.

[0040] Figure 2 The glass transition temperature (Tg) curve of the coating film prepared according to Example 1 after curing is obtained by differential scanning calorimetry. The test results show that the glass transition temperature of the coating film is 11.5℃.

[0041] Figure 3 This is a schematic diagram of an electrophoretic coating apparatus used in the cathodic electrophoretic coating of the present invention. The diagram shows the arrangement of the electrophoretic tank, stirring device, electrode system and workpiece to be coated (cathode plate).

[0042] Figure 4 The cationic acrylic resin prepared according to Example 1 was used to formulate a cathodic electrophoretic coating film, and then... Figure 3 The image shows the actual appearance of the cured coating obtained by electrophoretic coating performed using the apparatus shown, followed by crosslinking at 160°C for 30 minutes. Figure 4 As can be seen, the coating surface is smooth, uniform, and continuous, with high transparency and good decorative appearance.

[0043] Compared to existing epoxy cathodic electrophoretic coatings, epoxy resins contain aromatic benzene rings in their molecular chains. The conjugated π bonds on these benzene rings readily absorb light energy under ultraviolet radiation, triggering oxidative degradation reactions that lead to yellowing, loss of gloss, and chalking of the coating. Furthermore, the benzene ring structure imparts rigidity to the molecular chains, resulting in a brittle three-dimensional network after cross-linking. This network is prone to microcracks under alternating thermal stress, and the tight packing of epoxy resin chains makes it difficult to achieve high transparency. This invention uses cationic acrylic resin as the film-forming material. Both the acrylate and methacrylate monomers are aliphatic, lacking aromatic benzene rings in their molecular chains. The main chain formed after the carbon-carbon double bonds are opened and polymerized is a saturated carbon-carbon single bond structure. This structure absorbs ultraviolet light outside the solar spectrum, resulting in excellent lightfastness and outdoor durability. Simultaneously, the flexible alkyl segments of the acrylate monomer side chains impart good flexibility and crack resistance to the coating. The aliphatic structure also provides intrinsically high transparency, giving the coating excellent aesthetic appeal. Therefore, the cathodic electrophoretic coating prepared by this invention has outstanding flexibility, is not easily cracked by thermal cycling, and has excellent weather resistance and UV resistance, and is not prone to yellowing or chalking when used outdoors. The cathodic electrophoretic coatings obtained in Examples 1-5 were tested and showed a cross-cut adhesion rating of 0 and a pencil hardness of 3H.

[0044] The cathodic electrophoretic coating obtained in Example 1 was subjected to adhesion testing according to GB / T 9286-2021 "Paints and Varnishes Cross-cut Test". Specifically, a multi-blade cutting tool was used to cut right-angled grid patterns with a spacing of 1 mm on the coating surface, ensuring that the cuts penetrated the coating to the substrate. After cleaning the debris with a soft brush, pressure-sensitive adhesive tape was applied to the grid area and pressed firmly. Then, the tape was peeled off smoothly at a 60° angle. The peeling of the coating within the grid was observed under a magnifying glass and the grade was evaluated. It is understood that the specific embodiments described above are merely for explaining the relevant invention and not for limiting the invention. Furthermore, it should be noted that, for ease of description, only the parts relevant to the invention are shown in the accompanying drawings. Multiple technical solutions in the same embodiment, as well as multiple technical solutions in different embodiments, can be arranged and combined to form new technical solutions that do not contradict or conflict with each other. Any equivalent structural transformations made based on the content of this specification and drawings, whether directly or indirectly applied to other related technical fields, are similarly included within the scope of protection of this invention.

Claims

1. A method for preparing a cationic acrylic resin, characterized in that, Includes the following steps: S1. The first part of the oil-soluble initiator is dissolved in the monomer mixture, and the polymerization reaction is carried out by a continuous drop-addition process of free radical polymerization. The polymerization reaction temperature is 85~95℃ and the polymerization time is 3.5~4.0 hours. S2. After the polymerization reaction is completed, add the second part of oil-soluble initiator and keep it at the temperature for 1.5 to 2.0 hours. The sum of the mass of the first part of oil-soluble initiator and the second part of oil-soluble initiator accounts for 1-5% of the mass of the monomer mixture. S3. Cool down to 60~70℃, add organic acid to neutralize until the degree of neutralization is 75±5%, keep warm for 20~40 minutes and then discharge to obtain cationic acrylic resin; The monomer mixture includes monomers containing tertiary amine groups, monomers containing hydroxyl groups, methacrylate monomers, and acrylate monomers, and the total mass of the monomer mixture is denoted as M; The monomer containing a tertiary amine group accounts for 10-15% of M; The hydroxyl-containing monomer accounts for 15-20% of M; The mass ratio of the methacrylate monomer to the acrylate monomer is (4~3):2, and the sum of their masses accounts for 65~75% of M.

2. The method for preparing cationic acrylic resin according to claim 1, characterized in that, The monomer containing a tertiary amine group is selected from one or more of dimethylaminomethyl methacrylate, dimethylaminoethyl methacrylate, and dimethylaminoethyl acrylate.

3. The method for preparing cationic acrylic resin according to claim 1, characterized in that, The hydroxyl-containing monomer is selected from one or more of hydroxyethyl methacrylate, hydroxypropyl methacrylate, and hydroxypropyl acrylate.

4. The method for preparing the cationic acrylic resin according to claim 1, characterized in that, The acrylate monomers are selected from one or more of ethyl acrylate, propyl acrylate, butyl acrylate, and isooctyl acrylate.

5. The method for preparing the cationic acrylic resin according to claim 1, characterized in that, The methacrylate monomers are selected from one or more of methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, n-octyl methacrylate, and isooctyl methacrylate, or the methacrylate monomers may be partially or completely replaced with styrene.

6. The method for preparing the cationic acrylic resin according to claim 1, characterized in that, The first part of the oil-soluble initiator is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile, and benzoyl peroxide, and the second part of the oil-soluble initiator is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile, and benzoyl peroxide.

7. The method for preparing the cationic acrylic resin according to claim 1, characterized in that, In step S1, the monomer mixture and the first portion of the oil-soluble initiator are dissolved using an organic solvent; in step S2, the second portion of the oil-soluble initiator is dissolved using an organic solvent and then added in addition; the mass of the organic solvent accounts for 50±5% of the mass of the cationic acrylic resin; The organic solvent is selected from one or more of ethylene glycol butyl ether, propylene glycol methyl ether, and isopropanol; The organic acid is selected from one or more of formic acid, acetic acid, and lactic acid.

8. The method for preparing cationic acrylic resin according to claim 1, characterized in that, In step S1, the first portion of the oil-soluble initiator and the monomer mixture are first dissolved together in the first portion of the organic solvent, and then added dropwise to the reaction system at a constant pressure dropping funnel to carry out the free radical polymerization continuous dropping process.

9. A cathodic electrophoretic coating, characterized in that, The preparation includes an isocyanate curing agent, water, and a cationic acrylic resin prepared by any one of claims 1 to 9, wherein the mass ratio of the cationic acrylic resin, the isocyanate curing agent, and the water is (50 to 70):(15 to 30):(300 to 450).

10. An application of the cathodic electrophoretic coating as described in claim 9, characterized in that, The cathodic electrophoretic coating is applied to the surface of a metal workpiece and then baked at 140-170°C for 20-40 minutes to form a cured coating.